If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + 8y = -6 Solving -4 + 8y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 8y = -6 + 4 Combine like terms: -4 + 4 = 0 0 + 8y = -6 + 4 8y = -6 + 4 Combine like terms: -6 + 4 = -2 8y = -2 Divide each side by '8'. y = -0.25 Simplifying y = -0.25
| -4(10+2y)+8y=-6 | | 3/4x-1/2=1/3 | | 3x+2(x+16)=77 | | 15xa=165 | | x+y+z=0.5 | | 8y^3-2y^2-y=0 | | log(x+15)+log(x+115)=5 | | 3y=(x+z) | | 2(3x-7)-(x-4)=5.x | | 3ln(c+5)=21 | | 1/4s=23 | | 1/8s=24 | | 2y-74=28 | | 5x+20y+16z=5.75 | | 27a-9b/8b-24a | | 5x+16=86 | | 2v^2-20v+42=(v-7)2 | | ln(0,5)/ln(0,87) | | 0=3x^2-5/2x-16/3 | | 1/2(5h)^2=1440 | | 1/2(5h)^2 | | sqrtx^2+x-2=2 | | (4x-7)(x-3)=0 | | (x-9)(2x+2)=-4(x-9) | | 5y+19=3y-37 | | =3xy-5z | | x^2+y^2+8x-8y-47=0 | | f(n)=f(4-1)+2(4) | | 3=1.06x | | 1/4x=1/7 | | f(4)=f(n-1)+2(4) | | 8+2t-7=9t+17-5t |